Clinical and dosimetric predictors of radiation-induced rhinosinusitis following VMAT for nasopharyngeal carcinoma: A retrospective study - Xiaomin Bao; Yan Wang; Bin Li; Liang Peng; Bin Ouyang; Chew Lip Ng; Yongshi Zhuo; Qiumin Wang; Chunwei Li; Jian Li (Heliyon, 2024)
Background: We aimed to investigate the clinical and dosimetric factors associated with radiation-induced rhinosinusitis, and further elucidate the optimal dose-volume constraints for nasopharyngeal cancer patients who underwent volumetric-modulated arc therapy (VMAT). Methods: A retrospective review of 196 nasopharyngeal carcinoma (NPC) patients who underwent definitive VMAT between August 2018 and May 2021 was conducted. Both clinical and dose-volume histogram (DVH) data of NPC patients without rhinosinusitis at baseline were selected for analysis. Results: The cumulative incidence of post-RT rhinosinusitis at the 3-, 6-, 9-, and 12-months, and >1 year were 29.6 %, 41.3 %, 42.9 %, and 45.4 %, and 47.4 %, respectively. Nasal irrigation was negatively associated with post-RT rhinosinusitis (p < 0.001). Higher cumulative incidences of maxillary and ethmoid sinusitis were associated with V70 > 1.16 % and >1.00 %, respectively (p = 0.027 and p = 0.002). Sphenoid sinusitis was more frequent when Dmax(maxillary sinus) exceeded 69.2Gy (p = 0.005). Conclusions: Regular nasal irrigation may reduce the development of rhinosinusitis. Dose-volume constraints of V70 and Dmax to the maxillary sinus are suggested for VMAT planning. Patients exceeding these thresholds should be closely monitored and potentially offered preventative interventions within 3–6 months post-RT.